2012
DOI: 10.1007/s00227-012-1883-z
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between the seasonal distribution of harbour porpoises and their prey in the Sound, Baltic Sea

Abstract: Low densities of harbour porpoises in winter (November-March) and high densities in summer (AprilOctober) were found in the Sound, connecting the Baltic Sea and Kattegat. Due to their high energy requirements, it is hypothesized that the density of harbour porpoises is related to local prey abundance. This was tested by examining the stomach content of 53 harbour porpoises collected between 1987 and 2010 in the Sound (high season, 34 porpoises; low season, 19 porpoises). A total of 1,442 individual Wsh specime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
44
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(47 citation statements)
references
References 36 publications
3
44
0
Order By: Relevance
“…The importance of environmental factors such as currents, chlorophyll and nutrients was also confirmed by Danish and German studies (Edrén et al 2010, Gilles et al 2011, Sveegaard et al 2012a. In the Belt Sea and Kattegat, the geographic distribution of porpoise concentrations appeared fairly stable when acoustic detection rates provided a pattern similar to the distribution of satellite-tagged animals averaged over 10 yr (Sveegaard et al 2011b).…”
Section: Seasonal Occurrence and Trends In Harbour Porpoise Presencementioning
confidence: 65%
See 1 more Smart Citation
“…The importance of environmental factors such as currents, chlorophyll and nutrients was also confirmed by Danish and German studies (Edrén et al 2010, Gilles et al 2011, Sveegaard et al 2012a. In the Belt Sea and Kattegat, the geographic distribution of porpoise concentrations appeared fairly stable when acoustic detection rates provided a pattern similar to the distribution of satellite-tagged animals averaged over 10 yr (Sveegaard et al 2011b).…”
Section: Seasonal Occurrence and Trends In Harbour Porpoise Presencementioning
confidence: 65%
“…Only 2 previous studies of satellite-tagged harbour porpoises were able to show seasonal movements, possibly also linked to changes in prey distribution (Read & Westgate 1997, Sveegaard et al 2012a. Sveegaard et al (2011a, p. 241-242) emphasized, however, that the observed seasonal movement patterns were not temporally coordinated migrations, but rather 'a seasonal change in im portance of some […] areas' and 'a gradual overall movement over a longer period'.…”
Section: Seasonal Occurrence and Trends In Harbour Porpoise Presencementioning
confidence: 95%
“…In particular, it is suggested that a relatively higher abundance of harbour porpoise in spring and summer can be expected in the central North sea, due to seasonal porpoise population movement from coastal areas to offshore areas (Gilles et al, 2009(Gilles et al, , 2016. Such seasonality in occurrence of marine mammals close to O&G platforms could be natural, and reflect a change in prey availability (De Boer, 2010;Sveegaard et al, 2012;Fujii, 2015;Gilles et al, 2016). On the other hand, the combined effect of shorter days and harsher weather conditions significantly reduces the likelihood of detecting marine mammals based on visual surveys (Clarke, 1982;Teilmann, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, changes in water temperature and chemical composition, as well as reproductive state and food availability, may influence the lipid and protein composition of prey, thereby shifting the energetic cost-benefit of that particular prey item (Di Beneditto et al, 2009;Spitz and Jouma'a, 2013). In the Baltic Sea, herring (Clupea harengus) have been shown to increase their energy density by up to 250% between seasons (Sveegaard et al, 2012). The energy density of prey can change at the ecosystem level as well as high quality species being removed by human or climatic pressures and replaced by lower quality species (Spitz and Jouma'a, 2013).…”
Section: Seasonal Energy Content and Prey Qualitymentioning
confidence: 99%